The political economy of Tanzania's decline and recovery - Lofchie, Michael F. (University of Pennsylvania Press, 2014)
Written by a leading thinker in the politics of the developing world, The Political Economy of Tanzania presents a compelling analysis of Tanzania's postindependence history. This insightful critique of development economics offers crucial lessons for scholars and policy makers with a stake in Africa's future